Competition in shoreline plant communities: A comparative approach. - Gaudet, Connie Lee. (University of Ottawa (Canada), 1993)
I tested the general hypothesis that competitive ability is an important determinant of pattern in shoreline plant communities. Specifically I tested four predictions generated from this general hypothesis: (1) the competitive performance of plant species is related to their distribution along natural gradients of fertility and standing crop; (2) the competitive performance of plant species is related to measurable plant traits; (3) the competitive performance of plant species is not significantly affected by changing nutrient supply; and (4) there is an "evolutionary trade-off" between nutrient stress tolerance of species and competitive performance that underlies the distribution of species along natural gradients of fertility and standing crop. These questions were posed at a broad, multi-species scale using comparative measures of competitive performance, stress tolerance, and morphology from over 40 shoreline plant species, and field distribution data from several natural shoreline communities in Ontario, Nova Scotia and Quebec. Results showed that the experimentally determined measure of the relative competitive performance of a species was significantly correlated with its position along natural gradients of fertility and standing crop; and with simple measurable plant traits, in particular above-ground biomass (r$\sb{\rm s}$ = 0.92; p .0001). Results also showed that the competitive performance of species under high and low nutrient conditions was significantly correlated after two growing seasons (r$\sb{\rm s}$ = 0.76; P .001); and that stress tolerance, measured as the relative biomass production of species under low nutrient conditions, was inversely correlated with competitive performance (r = $-$0.62, p .005).
Keywords: Biology, Botany.